ONTOLOGICAL SECURITY DALAM KOMUNIKASI AGEN DAN NASABAH ASURANSI (STUDI PADA AGEN DAN NASABAH PT ASURANSI JIWASRAYA (PERSERO) PEKANBARU) - Imadah Thoyyibah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This study aims to determine the psychological ontological security resources that are built psychologically in communication between insurance agents and customers that affect perceptions, thoughts, feelings and perspective of agents and customers of security and safety needs, especially in PT Asuransi Jiwasraya (Persero) Pekanbaru City . This research is descriptive qualitative using the method of observation, interview, documentation and library research. The results of research on ontological security sources in communication between insurance agents and customers at PT Asuransi Jiwasraya (Persero) Pekanbaru come from interpersonal communication processes between agents and customers that are established through relational relationships, the intensity of encounters, personal attention, empathy, and social ethics. Ontological security is characterized by a sense of security of agents and customers of ownership, stability, positive feelings (trust), self-identity, and physical presence. Based on the theory of needs hierarchy, the ontological security possessed by agents and clients is built after the fulfillment of physiological needs such as clothing, food, and shelter. Customer perception of the existence of security guarantees provided by insurance is influenced by the competence of agents in communicating interpersonal, transactional, and relational factors, in addition to the presence of a company's image stability.